How does context affect interventions to improve patient safety? An assessment of evidence from studies of five patient safety practices and proposals for research. Issue 7 (13th April 2011) - Øvretveit, John C; Shekelle, Paul G; Dy, Sydney M; McDonald, Kathryn M; Hempel, Susanne; Pronovost, Peter; Rubenstein, Lisa; Taylor, Stephanie L; Foy, Robbie; Wachter, Robert M
Abstract : Background: Logic and experience suggest that it is easier in some situations than in others to change behaviour and organisation to improve patient safety. Knowing which 'context factors' help and hinder implementation of different changes would help implementers, as well as managers, policy makers, regulators and purchasers of healthcare. It could help to judge the likely success of possible improvements, given the conditions that they have, and to decide which of these conditions could be modified to make implementation more effective. Methods: The study presented in this paper examined research to discover any evidence reported about whether or how context factors influence the effectiveness of five patient safety interventions. Results: The review found that, for these five diverse interventions, there was little strong evidence of the influence of different context factors. However, the research was not designed to investigate context influence. Conclusions: The paper suggests that significant gaps in research exist and makes proposals for future research better to inform decision-making.